Effects of Different Drying Methods on the Structural Characteristics and Multiple Bioactivities of Rosa roxburghii Tratt Fruit Polysaccharides - Qiuqiu Zhang; Sha Wu; Qinghua Dai; Peng Hu; Guangjing Chen (Foods, 2024)
Drying conditions significantly impact the compositions and microstructures of polysaccharides, leading to various effects on their chemical characteristics and bioactivities. The objective of this study was to investigate how different industrial drying techniques, i.e., hot air drying, infrared drying, microwave vacuum drying, and freeze drying, affect the structural properties and biological activities of polysaccharides extracted from Rosa roxburghii Tratt fruit (RRTP). Results revealed that these drying methods significantly altered the extraction yield, molecular weights, monosaccharide ratios, contents of uronic acid and total sugars, gelling properties, particle sizes, thermal stability, and microstructures of RRTPs. However, the monosaccharide composition and functional groups of polysaccharides remained consistent across the different drying techniques. Biological activity assays demonstrated that RRTPs, particularly those processed through microwave vacuum drying (MVD-RRTP), exhibited excellent anti-linoleic acid oxidation, robust anti-glycosylation effects, and significant α-glucosidase inhibition in vitro. The outcomes of this research demonstrate that microwave vacuum drying serves as an effective pre-extraction drying method for RRTPs, enhancing their biological activities. This technique is particularly advantageous for preparing RRTPs intended for use in functional foods and pharmaceuticals, optimizing their health-promoting properties for industrial applications.